Machining and CNC technology - Fitzpatrick, Michael (McGraw-Hill, 2011)
Part 1 presents the basic modern integrated manufacturing. Part 2 shows students how to safely set up and run manually operated machines. Part 3 deals with the goal of transferring manual skills to the CNC systsystem. Part 4 covers advanced and advancing technologies, further emphasizing the contemporary outlook of Fitzpatrick's book